Joint preoperative transthoracic and intraoperative transoesophageal echocardiographic assessment of functional mitral regurgitation severity provides better association with long-term mortality. (13th December 2020) - Asher, Shyamal R; Malzberg, Gregory W; Ong, Chin Siang; Malapero, Raymond J; Wang, Huan; Shekar, Prem; Kaneko, Tsuyoshi; Pelletier, Marc P; Mallidi, Hari; Heydarpour, Mahyar; Shook, Douglas C; Shernan, Stanton K; et al.
Abstract: OBJECTIVES: Functional mitral regurgitation (MR) is observed with ischaemic heart disease or aortic valve disease. Assessing the value of mitral valve repair or replacement (MVR/P) is complicated by frequent discordance between preoperative transthoracic echocardiographic (pTTE) and intraoperative transoesophageal echocardiographic (iTOE) assessment of MR severity. We examined the association of pTTE and iTOE with postoperative mortality in patients with or without MR, at the time of coronary artery bypass grafting (CABG) and/or aortic valve replacement without MVR/P. METHODS: Medical records of 6629 patients undergoing CABG and/or aortic valve replacement surgery with or without functional MR and who did not undergo MVR/P were reviewed. MR severity assessed by pTTE and iTOE were examined for association with postoperative mortality using proportional hazards regression while accounting for patient and operative characteristics. RESULTS: In 72% of 709 patients with clinically significant (moderate or greater) functional MR detected by pTTE, iTOE performed after induction of anaesthesia demonstrated a reduction in MR severity, while 2% of patients had increased severity of MR by iTOE. iTOE assessment of MR was better associated with long-term postoperative mortality than pTTE in patients with moderate MR [hazard ratio (HR) 1.31 (1.11–1.55) vs 1.02 (0.89–1.17), P -value for comparison of HR 0.025] but was not different for more than moderate MR [1.43 (0.96–2.14) vs 1.27 (0.80–2.02)]. CONCLUSIONS: In patients undergoing CABG and/or aortic valve replacement without MVR/P, these findings support intraoperative reassessment of MR severity by iTOE as an adjunct to pTTE in the prediction of mortality. Alone, these findings do not yet provide evidence for an operative strategy. Graphical Abstract: